Thinking, knowing, acting : epistemology and ethics in Plato and ancient Platonism - Bonazzi, Mauro, 1973-; Ulacco, Angela; Forcignanò, Filippo (Brill's Plato Studies Series, 2019)
The volume Thinking, Knowing, Acting: Epistemology and Ethics in Plato and Ancient Platonism aims to offer a fresh perspective on the correlation between epistemology and ethics, a topic of central importance in the Platonic tradition which has not yet received the attention it deserves. The first part deals with the social, juridical premises of Plato's philosophy, with particular regard to the relation between science and practical reason. The second part investigates the reception and development of these problems in Aristotle and the Platonic tradition. Other papers, on Solon and Galen, show that the conflict between knowledge and political action was also a central topic for the other Greek thinkers and contribute by contrast to a better evaluation of the originality of Platonism.